Potential biocontrol of fumonisin b1 production by fusarium verticillioides under different ecophysiological conditions in maize - Samsudin, Nik Iskandar Putra Bin (Cranfield University, 2015)
Fusarium verticillioides contaminates maize with the fumonisin group of mycotoxins for which there are strict legislative limits in many countries including the EU. The objectives of this project were (a) to examine the microbial diversity of maize samples from different regions and isolate potential biocontrol agents which could antagonize F. verticillioides and reduce fumonisin B1 (FB1) production, (b) to screen the potential biocontrol candidates using antagonistic interaction assays and different ratios of inoculum on maize-based media and on maize kernels to try and control FB1 production, (c) to examine whether the potential control achieved was due to nutritional partitioning and relative utilization patterns of antagonists and pathogen, and (d) to examine the effects of best biocontrol agents on FUM1 gene expression and FB1 production on maize cobs of three different ripening stages. ...[cont.]